Mechanisms of antidiabetogenic and body weight-lowering effects of estrogen in high-fat diet-fed mice - Bryzgalova, Galyna (American Physiological Society, 2008)
The high-fat diet (HFD)-fed mouse is a model of obesity, impaired glucose tolerance, and insulin resistance. The main objective of this study was to elucidate the molecular mechanisms underlying the antidiabetogenic and weight-lowering effects of 17β-estradiol (E(2)) in this mouse model. C57BL/6 female mice (8 wk old) were fed on a HFD for 10 mo. E(2), given daily (50 μg/kg sc) during the last month of feeding, decreased body weight and markedly improved glucose tolerance and insulin sensitivity. Plasma levels of insulin, leptin, resistin, and adiponectin were decreased. We demonstrated that E(2) treatment decreased the expression of genes encoding resistin and leptin in white adipose tissue (WAT), whereas adiponectin expression was unchanged. Furthermore, in WAT we demonstrated decreased expression levels of sterol regulatory element-binding protein 1c (SREBP1c) and its lipogenic target genes, such as fatty acid synthase and stearoyl-CoA desaturase 1 (SCD1). In the liver, the expression levels of transcription factors such as liver X receptor α and SREBP1c were not changed by E(2) treatment, but the expression of the key lipogenic gene SCD1 was reduced. This was accompanied by decreased hepatic triglyceride content. Importantly, E(2) decreased the hepatic expression of glucose-6-phosphatase (G-6-Pase). We conclude that E(2) treatment exerts antidiabetic and antiobesity effects in HFD mice and suggest that this is related to decreased expression of lipogenic genes in WAT and liver and suppression of hepatic expression of G-6-Pase. Decreased plasma levels of resistin probably also play an important role in this context.